Common mechanisms in intelligence and development: A study of ability profiles in mental age-matched primary school children - Baughman, Frank; Thomas, M.; Anderson, M.; Reid, C. (2016)
Background and aims: We examine the relationship between individual differences and cognitive development in order to address the question of whether variability in each might be due to common mechanisms. In two experiments, we compare the cognitive profiles of groups of younger and older children matched on overall mental age (MA) using standard tests of intelligence (British Abilities Scales-II; BAS-II, and Wechsler Intelligence Scale for Children, 3rd edition; WISC-III). Results: In both experiments, MANOVAs revealed few differences in the profiles of younger and older MA-matched children. In Experiment 1, no reliable differences were found on the six BAS-II core scales, and only one group difference was found on the supplementary, Speed of Processing diagnostic test, where the older children outperformed the younger children. In Experiment 2, analyses of the 10 core scales of the WISC-III revealed two group differences. These were on Coding, where the younger children's performance was superior to the older children, and on Arithmetic, where the older children outperformed the younger children.Conclusions: The degree of similarity between cognitive profiles of younger and older MA-matched groups suggests that a common mechanism may indeed underlie variability in individual differences and development. The findings further suggest that children of different ages, who are of the same overall ability level, are at the same developmental and intellectual level. However, further research is needed to determine just how similar ability-matched children remain over the course of development.